دور الأمثال الشعبيـــة السوفيـــــة في الحفاظ على الموروث -دراسة موضوعاتية - زغوان, اسراء; دادة, شيماء; رجيل, هيفاء (جامعة الوادي - University of Eloued, 2023)
دور الأمثال الشعبية السوفية في الحفاظ على الموروث نتاجا أدبيا يستحق الدراسة والتحليل لأنها فكرة شاملة عن ثقافة الإنسان الشعبي السوفي وطبيعته وبيئته التي عاش فيها, نجد أن الفرد السوفي حاول قدر الإمكان أن يحافظ على تراثه الشعبي كالمثل الشعبي الذي يتاورثه عن غيره, تحظى بقبول طوعى, وذلك لما تتمتع به هذه الأمثال من جمالية في الشكل وكثافة في المضمون وتنوع الموضوعات, كما أن الموروث الشعبي يحافظ على هوية الإنسان الشعبي من خلال الخبرات والتجارب التي مر بها وصياغتها في تلك العبارات القصيرة التي تلخص تجربة حياتية عاشها بين مختلف طبقات المجتمع فجاءت الامثال بالوان تحفظ موروثه دينيا وثقافيا بعبارات بليغة . Summary: The role of Soviet proverbs in preserving the popular heritage is a literary product that deserves study and analysis because it is a comprehensive idea of the culture of the Soviet folk, its nature and the environment in which it lived. This is due to the beauty of these proverbs in form, density of content, and diversity of topics, and the popular heritage preserves the identity of the popular person through experiences and experiences that he went through and formulated in those short phrases that summarize the life experience he lived among the various classes of society, so the proverbs came in conservative colors Inherited religiously and culturally in eloquent terms.
Keywords: المثل , الشعب , الموروث .; ideals, people, heritage.